Multiple forcing mechanisms determine geomorphology of Northumberland Strait, Canada - Shaw, John; Amos, Carl L.; Petrie, Brian (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
Analysis of multibeam sonar and LiDAR data permits interpretation of submarine landforms in eastern Northumberland Strait, part of the St. Lawrence Estuary system, eastern Canada. Landforms are interpreted in the light of multiple forcing mechanisms, principally: (1) glaciation; (2) postglacial relative sea-level fluctuations; (3) spatial variability of tidal currents; and (4) modern sea-ice impact. Bedrock exposures testify to relatively thin glacial sediments. Glacial landforms comprise ribbed moraines and glacial meltwater channels. The study area was emergent in the early Holocene, as evidenced by fluvial channels and former lakes in the Cape Tormentine area. Today, spatially varying tidal forces are strong determinants of geomorphology, and several landforms zones are identified: (1) tidal-swept zones at Abegweit Passage and Caribou, characterized by seafloor scour and scattered bedform fields; (2) the area of weak tidal circulation between the Abegweit and Caribou zones ‒ a low-relief sediment depocenter with littoral zone ridge-and-runnel beach systems, and estuaries; (3) transition zones located between the central depocenter and the tidal-current zones feature sediment drifts; (4) the tidal gyre at East Point, Prince Edward Island, which has formed Milne Bank; and (5) an area east of Caribou, where weaker tidal forces and stronger wave influence are evidenced by alongshore transport embayments between Milne Bank and Souris and the east-facing coast north of Cape Bear, where sediment is trapped in compartments isolated from one another. Modern sea-ice disturbance of the seabed (range -1 to -8 m) is most extensive in the Pictou Banks area.